Protective effect of β-cyclodextrin on stability of nisin and corresponding interactions involved. (1st November 2019) - Li, Jingjing; Pan, Dan; Yi, Juanjuan; Hao, Limin; Kang, Qiaozhen; Liu, Xin; Lu, Laizheng; Lu, Jike
Highlights: β-cyclodextrin showed protective effect on stability of nisin. Characterization revealed the interaction of β-cyclodextrin on nisin. A potential approach could be used to improve the stability of nisin. Abstract: Nisin has been extensively employed in food industry as an antimicrobial peptide, but the proteolytic degradation and interference by food components resulted in the decrease of its antimicrobial activity. This study intends to explore the protective effect of β-cyclodextrin (β-CD) on nisin and corresponding interactions involved. The antibacterial experiments indicated that the combination of nisin and β-CD could provide a better antibacterial effect on cooked pork meat. Spectral analysis with UV–vis and fluorescence spectroscopy showed that the micro-environment of nisin could be influenced by β-CD. Tricine-SDS-PAGE results exhibited that the combination of nisin and β-CD could delay the degradation of nisin and improve its stability in the presence of trypsin. In sum, the study provided a potential approach to improve the stability of nisin, especially in the presence of trypsin.